Isolation and Identification of Escherichia coli from Raw Vegetables in Kota Samarahan and Kuching, Sarawak - Lazarus Samuel, Ayi (Universiti Malaysia Sarawak (UNIMAS), 2011)
Escherichia coli is a gram negative and rod-shaped bacterium that is commonly found in the lower intestine of warm blood animals. Almost all E. coli strains are harmless, but some, such as serotype O157:H7 can cause serious food poisoning in humans due to the presence of Shiga-like toxin genes (slt). Eating contaminated raw food is one of the sources of transmission of E. coli. In this study, E. coli was isolated from various raw vegetables in Kuching and Kota Samarahan wet markets and supermarkets in Kuching and Kota Samarahan to determine the number of E. coli occurrences. The five main vegetables were cabbage, cucumber, tomato, winged bean, and carrot. Samples were first inoculated into an enrichment media of Luria Bertani (LB) broth while Eosin-Methylene Blue (EMB) agar was used for isolation. The isolates were tested through a series of biochemical tests. After that, multiplex-PCR assay was carried out to detect the presence of slt1 and slt2 genes in the E. coli positive samples. Subsequently, antibiotic susceptibility test for E. coli was determined via disk diffusion technique in determining the antibiotic susceptibility of E. coli isolates against a range of antibiotics. Through a series of biochemical test, 26 (28.89%) isolates were identified as E. coli while none of samples harbored slt1 and slt2 genes. All 26 samples were resistance toward erythromycin and sensitive toward nalidixic acid, tetracycline, nitrofurantoin, norfloxacin, and chloramphenicol. Seventeen samples were resistance toward ampicillin while 18 samples were resistance toward carbenicillin.